Feasibility and acceptability of an electronic immunization registry in urban Bangladesh - Md. Jawadul Haque; A. K. M. Kamruzzaman; Rajendra Bohara; Chiranjit Das; Md. Tarjumanul Haque Sanij; Abul Fazal Md. Shahabuddin Khan; F. A. M. Anjuman Ara Begum; Nazim Uzzaman (PLoS ONE, 2026)
Introduction Electronic Immunization Registries (EIRs) are increasingly being implemented in low- and middle-income countries (LMICs) to support immunization tracking and data management. In Bangladesh, an EIR was introduced in Rajshahi City Corporation (RCC) to strengthen routine immunization services. However, evidence on user perceptions and operational implementation in this context remains limited. We assessed perceptions related to the feasibility and acceptability of the EIR among caregivers and healthcare providers (HCPs) in an urban pilot setting. Methods We conducted a cross-sectional study between July and September 2024 in RCC, Bangladesh. Data were collected from caregivers of children receiving vaccinations and HCPs involved in immunization service delivery using a pretested semi-structured questionnaire. Perceptions of EIR-supported services were assessed using a 5-point Likert scale. Responses to open-ended questions were reviewed and summarized descriptively. This study was designed as a descriptive assessment and was not intended to evaluate the effectiveness or causal impact of the EIR system. Results A total of 321 participants were included, comprising 305 caregivers and 16 HCPs. Electronic registration was conducted primarily at the Expanded Program on Immunization centers (87%), with additional outreach through house-to-house visits. Reported vaccination uptake among children registered in the EIR system was high within the study sample. Caregivers and HCPs reported generally positive perceptions of EIR-supported services. Most respondents selected ‘satisfied’ or ‘highly satisfied’ responses across assessed items. HCPs also reported positive experiences, particularly in relation to record management and data accessibility, while noting operational challenges such as intermittent internet connectivity and device-related limitations. Conclusions The EIR was perceived as acceptable by caregivers and HCPs in this urban pilot setting. Further studies are needed to assess effectiveness, implementation challenges, and scalability across diverse settings.